A comparison of mechanical properties and X-ray tomography analysis of different out-of-autoclave manufactured thermoplastic composites. (October 2020) - Saenz-Castillo, Diego; Martín, María I; García-Martínez, Vanessa; Ramesh, Abhiram; Battley, Mark; Güemes, Alfredo
Three different out-of-autoclave manufacturing processes of CF/poly-ether-ether-ketone thermoplastic composites were characterized, including innovative laser-assisted automated fibre placement with in situ consolidation. Characterization techniques included differential scanning calorimetry, ultrasonic non-destructive testing and matrix digestion, in addition to 3D X-ray microcomputed tomography to investigate the void distribution, size and shape. The results revealed that in situ consolidation process can lead to the accumulation of large voids between the upper layers. Interlaminar shear, in-plane shear, tensile and flexure testing were used for mechanical evaluation. A reduction in the mechanical properties was observed for in situ consolidation laminates when compared to the other out-of-autoclave methods. The drop in mechanical properties of in situ consolidation laminates was mainly attributed to the differences found in void distribution and size. Optimization of processing parameters along with higher quality prepreg raw material could be of assistance for the improvement of mechanical properties of in situ consolidation structures.